Stability, Boundedness, and Square Integrability of Solutions of Neutral Fourth-Order Differential Equations - Rahmane, Mebrouk; Remili, Moussadek; D. Oudjedi., Linda (Armenian Journal of Mathematics, 2022)
The purpose of this paper is to establish a new result, which guarantees the asymptotic stability and boundedness of the zero solution and the square integrability of solutions and their derivatives to neutral type nonlinear differential equations of fourth-order. We illustrate our results by an example at the end of the paper.